The solution of the equation of minimal surface by finite-difference method - Agalcev, A.; Sapagovas, M. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. В. Агальцев, М. П. Сапаговас. Решение уравнения минимальной поверхности методом конечных разностей A. Agalcevas, M. Sapagovas. Minimalaus paviršiaus lygties sprendimas baigtinių skirtumų metodu